Hubungan Self-Esteem Dengan Perilaku Social Withdrawal Pada Dewasa Awal - Massie, Karen Clemency Benevolence; Arianti, Rudangta (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Self-esteem refers to an individual’s belief in their own worth and capacity to act effectively and cope with life challenges. Individuals with high self-esteem tend to experience better psychological well-being, whereas those with low self-esteem often perceive themselves as unworthy and incompetent. In response to stressful or challenging situations, individuals may adopt various coping behaviors, both physically and emotionally. One behavioral response that frequently emerges is social withdrawal, characterized by avoidance of social interaction and disengagement from the social environment. Social withdrawal can have negative implications for personal development, interpersonal relationships, and overall mental health, particularly during early adulthood, a developmental stage marked by significant social and emotional demands. This study aimed to examine the relationship between self-esteem and social withdrawal behavior among early adults. The research employed a quantitative approach with a correlational design. Data were analyzed to determine the presence and direction of the relationship between the two variables. The findings revealed that there was no significant relationship between self-esteem and social withdrawal behavior among early adults. These results suggest that self-esteem alone does not adequately explain the emergence of social withdrawal behavior. The implications of this study indicate that other psychological or contextual variables, such as social anxiety, coping strategies, personality traits, or environmental factors, may play a more substantial role in influencing social withdrawal. Therefore, future research is recommended to incorporate additional variables to obtain a more comprehensive understanding of social withdrawal behavior in early adulthood.